Pecularities of the Decretum Burchardi Wormatensis especially regarding the discipline about bishops and their duties - Díaz Moreno, José María (Revista española de derecho canónico, 2014)
When the Caroling World had disintegrated, between 1008 and 1022 the Decretum Burchardi Wormatensis canon law collection got a distinguished importance, especially in the Low Countries. Based on our above explained analysis clearly stands out a much more universal systematic canonical collection than before. This new collection was perfectly suitable to be a canon law handbook at many territories, and it could serve profoundly the daily canonical administration, the pastoral service of the clergy, but the canonical legislation too. Within this last on eshould be emphasized the conciliar legislation which can illustrate well by the decrees of Hungarian councils in the 11th-12th century. We can organize into five different groups of the Episcopal discipline of the Decretum Burchardi: selection and consecration of the suitable persons a bishop; personality of the bishop; duties of the bishop; bishop, metropolitan, and their relations including the provincial council; finally, the juridical protection of their relations including the provincial church; finally, the juridical protection of the particular authority of metropolitan and primate. Burchard's Collection is an extraordinary example for that goal how compilers of the canonical collections were intended to collect all of the ecclesiatical discipline as complete as possible, in order to promote not only the canonical knowledge, but the day to day administration of sacraments and sacramentals based on the clear canonical regulations